Meta-Analysis of Autoimmune Regulator-Regulated Genes in Human and Murine Models: A Novel Human Model Provides Insights on the Role of Autoimmune Regulator in Regulating STAT1 and STAT1-Regulated Genes - Lovewell, Thomas R. J.; McDonagh, Andrew J. G.; Messenger, Andrew G.; Azzouz, Mimoun; Tazi-Ahnini, Rachid (Frontiers in Immunology, 2018)
AIRE regulates promiscuous expression of tissue-restricted antigens (TRAs) in medullary epithelial cells (mTEC) of the thymus. To understand the diverse effects of AIRE, it is crucial to elucidate the molecular mechanisms underlying the process of AIRE-regulated gene expression. In this study, we generated a recombinant AIRE expression variant of the TEC 1A3 human cell line, TEC 1A3 AIREhi, to determine genes targeted by AIRE, and using microarray analysis, we identified 482 genes showing significant differential expression (P<0.05; FDR<5%), with 353 upregulated and 129 downregulated by AIRE expression. Microarray data were validated by QPCR, confirming the differential expression of 12 known AIRE-regulated genes. Comparison of AIRE-dependent differential expression in our cell line model with murine datasets identified 447 conserved genes with a number of transcription regulatory interactions, forming several key nodes, including STAT1 which had over 30 interactions with other AIRE-regulated genes. As STAT1 mutations cause dominant chronic mucocutaneous candidiasis and decreased STAT1 levels in monocytes of APS-1 patients, it was important to further characterise AIRE-STAT1 interactions. TEC 1A3AIREhi were treated with the STAT1 phosphorylation inhibitors fludarabine and LLL3 showed that phosphorylated STAT1 (p-STAT1) was not responsible for any of the observed differential expression. Moreover, treatment of TEC 1A3 AIREhi with STAT1 shRNA did not induce any significant variation in the expression of unphosphorylated STAT1 (U-STAT1) downstream genes, suggesting that these genes were directly regulated by AIRE but not via U-STAT1. The novel model system we have developed provides potential opportunities for further analysis of the pathogenesis of Autoimmune Polyglandular Syndrome 1 (APS1) and the wider roles of the AIRE gene.